Fawătih Al-Suwari: Reveal Esoteric Letters and Sentences in Holy Quran - Dian Berkah, Sri Warjiyati (International Journal of Advanced Science and Technology, 2020)
Al Quran as a holy book and revelation from Allah has special position in Muslim community. It acts as source of laws and guidance to maintain order in this worldly life and hereafter. Thus, interpretation of Holy Quran is an important knowledge in Muslim community since Prophet’s time until now. One part of Quranic interpretation and commentary knowledge is regarding Fawatih al-SuwariQuranic chapthers’ opening that have various forms, from a command sentences, requisite sentences and even only single Arabic or Hijaiya letter. These sentences and letters are believed to have esoteric meaning and they had invited many scholars, Muslims as well as orientalist with their theological and scientific background to research, discuss and even debate meaning behind these sentences and letters. This paper is aimed to reveal various forms of Quranic chapters’ opening or Fawatih al-Suwari, both sentences and letters as well as give description about opinions from scholars with their respective background regarding Fawatih al-Suwari. This paper concluded that existence of fawatih al-Suwari as part of mutashabihat verses has gained lots of attention from Quranic commentators, either from sufist, shia and even orientalists that interpret those letters and sentences with their respective opinions parallel with their background.